1991
DOI: 10.1021/es00014a012
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic distribution of carbon from sewage sludge and eutrophication in the sediments and food web of estuarine ecosystems

Abstract: Stable isotope ratios (513C) from samples of water, sediments, and biota traced the behavior of organic carbon for 3 summer months in estuarine mesocosms (three controls, three with added sewage sludge, three with added inorganic nutrients). Isotope ratios proved to be a useful quantitative tracer for sewage carbon as well as for the fresh phytoplanktonic carbon produced during nutrient fertilization. Sewage sludge sedimented within hours of its addition, and approximately 50% remained in sediments after 99 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…Two-way ANOVA results comparing biomass accumulation rate, N, C, and P percentages, and δ & Valiela 1998, Martinetto et al 2006, Oczkowski et al 2008. In addition, δ 13 C tends to be higher in eutrophic waters (Gearing et al 1991, Oczkowski et al 2008). The percentage of N and P in thalli of U. lactuca as well as in other macroalgal species increases with the availability of these elements in the environment (Pedersen & Borum 1996, 2008.…”
Section: Links Among Water Quality Internal Nutrient Pools and Macrmentioning
confidence: 95%
See 1 more Smart Citation
“…Two-way ANOVA results comparing biomass accumulation rate, N, C, and P percentages, and δ & Valiela 1998, Martinetto et al 2006, Oczkowski et al 2008. In addition, δ 13 C tends to be higher in eutrophic waters (Gearing et al 1991, Oczkowski et al 2008). The percentage of N and P in thalli of U. lactuca as well as in other macroalgal species increases with the availability of these elements in the environment (Pedersen & Borum 1996, 2008.…”
Section: Links Among Water Quality Internal Nutrient Pools and Macrmentioning
confidence: 95%
“…There is evidence that the δ 13 C in food web components and sediments from eutrophic estuaries are higher than in less productive waters (Gearing et al 1991, Oczkowski et al 2008). This pattern has been related to the uptake of HCO 3 -as a C source by macroalgae in nutrient-rich sea waters (Oczkowski et al 2008).…”
Section: Relative Effects Of Internal Nutrient Pools and Herbivory Onmentioning
confidence: 99%
“…He also found no dramatic difference between locations for the benthic animals examined and they appeared similar to the sediments, with δ 15 N of 9.4-11.4‰. The first use of δ 13 C to describe food chains in the bay also showed no difference between sediments in the West and East Passages or with depth in the sediments (Gearing et al 1984(Gearing et al , 1991). An important finding from these studies was that the heavy δ 13 C signature in benthic animals in the bay suggested that they were feeding preferentially on diatoms rather than Concentrations of HCO À 3 , CO 2 , and CO 2À 3 over a pH range of 6-9 at a salinity of 30.…”
mentioning
confidence: 93%
“…During a MERL mesocosm experiment involving the fertilization of lower Narragansett Bay waters with inorganic nutrients (DIN, dissolved inorganic P, and Si), Gearing et al (1991) observed that δ 13 C values of phytoplankton in the most nutrient-enriched mesocosm were an average of 4.3‰ heavier than phytoplankton in control mesocosms receiving no nutrient enrichment (δ 13 C=−17.3‰ compared with −21.6‰, respectively). This isotopic enrichment was also reflected in zooplankton and in all feeding types of the benthos.…”
mentioning
confidence: 99%
“…Plant uptake from sources of different isotope composition results in changes to their δ 15 N and δ 13 C values and follows a two component mixing model according to Gearing et al (1991), as shown in Eq. (1):…”
Section: Calculation Of 15 N and 13 C Uptakementioning
confidence: 99%